PERSEPSI PROVIDER MENGENAI RENCANA PENERAPAN KEBIJAKAN KELAS RAWAT INAP STANDAR (KRIS) DALAM PROGRAM JKN DI SALAH SATU RS SWASTA DI KAB. PEMALANG - Luvian, Quinta Olif; Indriyani, Yeni (Dian Nuswantoro Semarang, 2025)
This study aims to analyze the perceptions and readiness of healthcare providers in implementing the Standard Inpatient Class (Kelas Rawat Inap Standar/ KRIS) policy under the National Health Insurance (JKN) program in Indonesia. The study employed a quantitative descriptive method with a cross-sectional design involving 151 respondents who completed structured questionnaires. Data were analyzed using univariate and bivariate (Spearman Rank correlation) analysis. The results showed that most respondents (90%) agreed that hospitals should implement KRIS and recognized the existence of 12 essential criteria. A majority of respondents (88%–90%) believed that KRIS would improve inpatient service quality, ensure patient safety, enhance equity through a single class system, and increase access to standardized healthcare services. Regarding hospital readiness, most respondents (above 88%) agreed on the need for infrastructure improvement, addition of medical equipment, hiring specialists, staff training, investment, and partnerships. The Spearman Rank test showed a very strong and significant relationship (r = 0.712; p = 0.000) between providers’ perceptions and planned actions. These findings highlight that although providers show positive perceptions toward KRIS, substantial preparation and support are required to ensure successful implementation.